PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2016 - Dewi Nur Yuliani, 14.05.52.0156; Lisiantara, Greg. Anggana (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the effect of profitability, firm size, board of commissioner size, leverage and audit committee on Complete Disclosure of Corporate Social Responsibility in Banking Companies Listed on the Indonesia Stock Exchange for the 2014-2016 Period. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) and published financial statements from 2014 to 2016. This research is an empirical study using a sensus technique in sampling. The analytical tool used is normality test, classic assumption test, multiple linear regression test, model test and hypothesis test. Based on the research that has been conducted, the results of this study show that the Audit Committee has a significant positive effect on disclosure of Corporate Social Responsibility. While profitability, company size, board of commissioner size and leverage have no significant effect on disclosure of Corporate Social Responsibility.